'Sometimes I don't feel like an osteopath at all'- a qualitative study of final year osteopathy students' professional identities. (December 2017) - Clarkson, Holly J.; Thomson, Oliver P.
Abstract: Background: Research suggests that professional identity has implications for standards of professionalism, patient care and work satisfaction. Professional identity develops during professional education and continues into working life. While osteopaths' professional identities and conceptions of practice have been outlined, the professional identities of osteopathic students are yet to be elucidated. Objectives: To explore and describe final year osteopathy students' professional identities and their development. Method: Semi-structured interviews were conducted with a purposive sample of eight final year osteopathy students from two osteopathic education institutions in the UK. Interviews were transcribed verbatim and constructivist grounded theory was used to conceptualise, collect and analyse data. Results: Participants' professional identities varied and were illustrated by their thoughts and beliefs around their approach to patients, the osteopathic profession, learning experience and practice skills. There was also variation in the stages of development of participants' professional identities which lay on a continuum ranging from 'under construction', 'transitioning' and 'constructed'. Conclusions: The findings suggest that final year osteopathy students held differing professional identities, and four categories were constructed which describe this variation, these were: approach to patient care, view of osteopathy, learning experience and view of practical skills. Students' professional identities varied in their stages of development and related to three points along a profession identity continuum and are in accordance with role transition theory. A well-developed professional identity, which is also flexible in response to new knowledge and evidence, has positive connotations for students' confidence in practice, well-being and career success.